The Influence of Foreign Ownership, Environmental Certification, Board of Commissioners, Women Directors on Corporate Social Responsibility Disclosure - Rahman, Nadiah Ocvinitha; Savitri, Enni; Silfi, Alfiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study aims to analyze the effect of foreign ownership, environmental certification, board of commissioners, women directors on corporate social responsibility disclosure in manufacture companies listed on the Indonesia Stock Exchange (IDX) 2017-2021. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017–2021. The sampling method used was purposive sampling. There were 65 companies that met the criteria and became the research sample. The data analysis technique uses panel data regression with a random effect model. The results show that foreign ownership has an effect on CSR disclosure because foreigners are considered more concerned about corporate social responsibility. Environmental certification has an effect on CSR disclosure because certified companies expect their products to have a high reputation and be well received by the public and their stakeholders. The size of the board of commissioners has an effect on csr disclosure because of the authority they have, the board of commissioners can exert a strong enough influence to put pressure on management to disclose csr. Meanwhile, women directors has no effect on CSR disclosure due to the minimal percentage of women directors in the study compared to the presence of male directors. The results of this study are expected to provide an overview of the importance of social responsibility in companies. The company is not only seen as a profit-creating institution for the owners of capital, but also must be seen as an institution that creates community welfare by taking into account the sustainability of the environment in which the company operates, so that there is a balance between people, planet and profit in accordance with the Triple-P Bottom Line concept. The novelty of the research is the addition of women on directors variables using the upper echelon theory as well as being examined using the random effect model. Key words : Foreign ownership, environmental certification, board of commissioners, women on directors on corporate social responsibility disclosure.